If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8x-45-10=15+6x
We move all terms to the left:
8x-45-10-(15+6x)=0
We add all the numbers together, and all the variables
8x-(6x+15)-45-10=0
We add all the numbers together, and all the variables
8x-(6x+15)-55=0
We get rid of parentheses
8x-6x-15-55=0
We add all the numbers together, and all the variables
2x-70=0
We move all terms containing x to the left, all other terms to the right
2x=70
x=70/2
x=35
| 4b+12=84 | | B+9b+2=12 | | —16+z=20 | | /1x+11=15 | | 41/2x+7=12 | | 8/17=u/5 | | 7s-3s-4=20 | | 4.x=1/2 | | 1=12b | | -11-19b-16=-6+6(-5b-20) | | /x/1+11=15 | | 4.x=1/ | | 3z+5=z-8 | | 5(-10+m)=10 | | 3/7=u;11 | | -63=3(2n-29) | | 2(c+5)=3c+1 | | (u)/(16)=(5)/(8) | | 14c-12c+3=9 | | 16+3x=x+8 | | 10/2c=+2 | | -134=-2(8n-2)-7n | | 4x(x+3)=96 | | -15+4r=-9 | | -7(p+9)=14 | | 3x+6x-5=50 | | 10=y/3=6 | | -14h-2=13-11h | | 36=-9(-8+n) | | x-(0.25x)=25000 | | |u|=3 | | 5x=5x=5x |